(untitled) (Physical Education, Health and Social Sciences, 2025)
This study investigated the relationship between toxic masculinity ™ and emotional intelligence (EI) across gender groups, with the aim of clarifying whether rigid masculine norms undermine or align with emotional competencies. Using a sample of 151 participants, correlational and regression analyses were conducted. At the aggregate level, the hypothesized negative association between TM and EI was not supported. The overall correlation was weak and nonsignificant, r(151) = .109, p = .184 (Table 7), and regression analyses confirmed that TM explained only 1.2% of the variance in EI, F(1, 149) = 1.779, p = .184, with a nonsignificant slope, B = 0.166, SE = 0.125, β = .109, t(149) = 1.334, p = .184 (Tables 8–10). Residual diagnostics indicated substantial unexplained variance, with residuals ranging from –82.463 to 80.377 and a standard deviation of 34.547 (Table 11). Subgroup analyses, however, revealed significant gender-based differences. Among men, TM was positively associated with EI, r(65) = .303, p = .014 (Table 12), suggesting that masculine traits such as assertiveness and emotional control may overlap with self-perceived emotional regulation and social influence. Among women, TM was negatively associated with EI, r(67) = –.331, p = .006 (Table 13), indicating that adopting rigid masculine norms may conflict with cultural expectations of empathy and relational sensitivity, thereby reducing EI. Among participants who preferred not to disclose gender, the association was weak and nonsignificant, r(19) = –.069, p = .780 (Table 14), likely reflecting heterogeneity in identity and socialization experiences. These findings confirm that gender moderates the TM–EI relationship, with opposing directions of association across groups. The results highlight the importance of considering gender role socialization and cultural context in understanding how masculinity norms intersect with emotional competencies (Connell & Messerschmidt, 2005; Vandello & Bosson, 2013). While the overall relationship was nonsignificant, the subgroup analyses provide compelling evidence that the TM–EI nexus is contingent on gender identity. Future research should employ larger and more diverse samples, facet-level analyses of both TM and EI, and advanced modeling techniques such as structural equation modeling (Kline, 2016). Applied implications include the need for gender-sensitive interventions: leveraging positive masculine traits for men, reducing the internalization of restrictive norms for women, and ensuring inclusivity for gender-diverse individuals (Day & Dragoni, 2015).